2017
DOI: 10.4236/am.2017.89096
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of US Sector of Services with a New Fama-French 5-Factor Model

Abstract: In this paper, we empirically test a new model with the data of US services sector, which is an extension of the 5-factor model in Fama and French (2015) [1]. 3 types of 5 factors (Global, North American and US) are compared. Empirical results show the Fama-French 5 factors are still alive! The new model has better in-sample fit than the 5-factor model in Fama and French (2015).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…This innovative asset pricing factor model is applied in recent researches about investment allocation strategies (Angelidis -Tessaromatis 2017), the analysis of US service sector (Yang et al 2017), and testing the five-factor model for different stock markets (Harshita et al 2015;Chia et al 2016;Guo et al 2017;Fama -French 2017, among others). It should be noted that there is a shortage of papers analysing the impact of the factors proposed by FF5 on the Spanish stock market, especially at company level.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…This innovative asset pricing factor model is applied in recent researches about investment allocation strategies (Angelidis -Tessaromatis 2017), the analysis of US service sector (Yang et al 2017), and testing the five-factor model for different stock markets (Harshita et al 2015;Chia et al 2016;Guo et al 2017;Fama -French 2017, among others). It should be noted that there is a shortage of papers analysing the impact of the factors proposed by FF5 on the Spanish stock market, especially at company level.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Fama and French five-factor model not only applies well to Borsa Istanbul (BIST), but also explains variations in excessive portfolio returns (Acaravci & Karaomer, 2017;Yang et al, 2017), and is able to offer a better description of emerging market equity returns (Foye, 2018). Huang (2019) confirmed that the FF five-factor model is superior to other traditional asset pricing models in explaining individual stock returns in China.…”
Section: Introductionmentioning
confidence: 76%
“…Third, a summary asset pricing test was employed whether the five-factor model returns lower intercepts than the three-factor version. Foye concluded at last that the performance of the five-factor model is better than the three-factor in Eastern Europe and Latin America, but in Asia, the results show not much difference [3] 2) The new model fits the data better than Fama-French (2015)'s 5-factor model [4]. The outbreak of the new crown has had a huge impact on the U.S. investment market.…”
Section: Related Researchmentioning
confidence: 95%
“…After that, many new factor models are also developed. Many empirical results show Fama-French five-factor model is capable of explaining the stock returns better than the CAPM [1]. Hence, applying the Fama-French fivefactor model is helpful to figure out the factors that determine the return rate of a specific stock or sector.…”
Section: Introductionmentioning
confidence: 99%